Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) TK Pembangunan Laboratorium UNP - Hafizah Ali; Gina Dwi Permata Sari ; Wilda Febriyanti; Afifa Ahrani (Populer: Jurnal Penelitian Mahasiswa, 2024)
Abstract. Implementation of the Merdeka Curriculum with a focus on the Project for Strengthening the Pancasila Student Profile (P5) has become a major concern in the world of education since 2022. This research aims to understand the implementation of P5 in the UNP Laboratory Development Kindergarten, focusing on the topics of implementation, objectives, benefits, advantages, and evaluation. The research method involves collecting data through observation, interviews, and documentation studies. The research results show that the implementation of P5 in the UNP Laboratory Development Kindergarten has had a positive impact in increasing understanding of the values ​​of Pancasila, introducing local culture, and forming character and environmental awareness in kindergarten children. Evaluation of P5 activities is carried out through learning management and involving active participation from the surrounding community. In conclusion, the implementation of P5 in the UNP Laboratory Development Kindergarten makes a positive contribution to improving the quality of learning, building student character, and community participation and empowerment. The suggestion proposed is the need for cooperation between teachers, P5 coordinators, and parents of students to better adapt the P5 program.